Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1063/1.2992632
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reaction with XeF2 on surface adhesion of Al and Al2O3 surfaces

Abstract: The change of surface adhesion after fluorination of Al and Al 2 O 3 surfaces using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…SEM images of AFM tips revealed the tip radius of 30-40 nm. Because the contact AFM experiment was carried out at the low load (< 5 nN), the change of tip radius was ignorable, as confirmed with SEM images taken after the AFM experiment (20). SEM analysis is performed with a Variable Pressure Field Emission SEM Model S-4300SE/N (Hitachi).…”
Section: Methodsmentioning
confidence: 99%
“…SEM images of AFM tips revealed the tip radius of 30-40 nm. Because the contact AFM experiment was carried out at the low load (< 5 nN), the change of tip radius was ignorable, as confirmed with SEM images taken after the AFM experiment (20). SEM analysis is performed with a Variable Pressure Field Emission SEM Model S-4300SE/N (Hitachi).…”
Section: Methodsmentioning
confidence: 99%
“…3(a) [23,32]. Multiple measurements were made, with a total of 10 consecutive approachewithdrawal cycles on each site.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, for various materials (e.g., nanoparticles [20], nanowires [21], and tetrapods [22]), AFM FD spectroscopy was utilized to investigate the influence of surface modification on adhesion force. For example, Zhang et al demonstrated adhesion enhanced by AlF 3 , which is generated during the XeF 2 etching process [23]. Park et al reported that adhesion between atomically clean quasicrystals and an AFM tip is weakened by adsorption of adsorbate molecules [24].…”
Section: Introductionmentioning
confidence: 98%
“…However, there is also a third peak that can be observed for as-deposited samples which is located at 77 eV. The literature is very scant on that matter, there is a record on Al-F bond located at 77 eV [37], however, no fluoride has been detected in our wide spectra, which is why this third peak more likely belongs to the Al-O bond affected by nitrogen as this is suggested by P.W. Wang et al [38].…”
Section: X-ray Photoelectron Spectroscopy (Xps) Datamentioning
confidence: 99%